Trend Analysis of Character Education in Mathematics Learning in Indonesia Over A Decade - Yuni Fitriyah; Wahyudin Wahyudin; Turmudi Turmudi; Hanifah Nurhayati; Fitria Maghfiroh (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2024)
Character education is a critical component in 21st-century education, serving not merely as a means to foster academic dimensions, but also as a foundational cornerstone in shaping moral and ethical values among students. This study aims to conduct a bibliometric analysis of recent developments and trends in character education research in mathematics learning in Indonesia over the past decade. The method utilized was bibliometric analysis, primarily condu cted through searches in the Dimensions database using the phrases